Sedimentary protolith and high-P metamorphism of oxidized manganiferous quartzite from the Lanterman Range, northern Victoria Land, Antarctica - Kim, Taehwan; Kim, Yoonsup; Tumiati, Simone; Kim, Daeyeong; Yi, Keewook; Lee, Mi Jung (European Journal of Mineralogy, 2024)
Abstract. We investigated the mineral assemblage, mineral and bulk-rock chemistry, and zircon U–Pb age of a manganiferous quartzite layer in the Lanterman Range, northern Victoria Land, Antarctica. The mineral assemblage consists primarily of phengite and quartz, along with spessartine-rich garnet, Mn3+ and rare earth element–yttrium (REY)-zoned epidote-group minerals, and titanohematite. Mineral inclusions such as tephroite, rutile and pyrophanite are hosted in porphyroblasts of the latter three minerals and suggest prograde blueschist-facies to low-T eclogite-facies metamorphism (M1). Epidote-group minerals commonly exhibit multiple growth zones of piemontite and/or epidote (M1), REY-rich piemontite (M2), REY-rich epidote (M3), and epidote (M4) from core to rim. Pseudobinary fO2–X diagrams at constant P–T support the stability of an epidote-group mineral-bearing assemblage under highly oxidized conditions during prograde M2 to peak M3 metamorphism. In marked contrast, tephroite-bearing assemblages (M1) are limited to relatively reduced environments and Mn-rich, silica-deficient bulk-rock compositions. Mn nodules have such characteristics, and the contribution of this hydrogenous component is inferred from bulk-rock chemical features such as a strong positive Ce anomaly. The major-element composition of the manganiferous quartzite suggests a protolith primarily consisting of a mixture of chert and pelagic clay. The presence of rare detrital zircons supports terrigenous input from a craton and constrains the maximum time of deposition to be ca. 546 Ma. The lack of arc-derived detrital zircons in the quartzite and the predominance of siliciclastic metasedimentary rocks among the surrounding rocks suggest that the deep-sea protolith was most likely deposited in an arc/back-arc setting at a continental margin. High-P metamorphism associated with terrane accretion during the Ross orogeny took place in the middle Cambrian (ca. 506 Ma), broadly coeval with the metamorphic peak recorded in the associated ...